Health service provision for women 50+: the "Frauen 5.0" project in the north-east region in Germany. (13th November 2019) - Dini, L; Pruetz, F
Abstract: Background: A higher life expectancy for women in Germany coincides with shortages in health professionals. Besides gynecologists (Gyn), the main providers of ambulatory healthcare services for women 50+ are general practitioners (GPs), which are not providing any gynecological services. The project "Frauen 5.0" aims to identify strategies for improving health care provision for women 50+ in three north-east states of Germany by analyzing health system indicators and exploring the perspective of service providers, users, practitioners and policy makers. Methods: Mixed-methods combined with participatory research including 1) secondary data analysis (Robert Koch-Institute and Zentralinstitut); 2) postal quantitative survey of all Gyn (n = 1.031) and of a randomized sample of 66% of GPs (n = 3.514); 3) qualitative interviews of women 50 + (n = 25); and 4) round tables with practitioners and policy makers. Results: In Germany 25% of the population are women 50+, from which 41% do not use Gyn services. Users expressed the need that GPs/Gyn actively address women's health issues during consultation. The survey (response rate 51% Gyn; 25% GPs) revealed a high willingness to collaborate among GPs and Gyn. Barriers and synergies in organizational, professional and user aspects were identified. Task-sharing between GP and Gyn, delegation to non-medical personnel and the introduction of financial incentives showed to be a key element to improve health care services for women 50+. Dissusion: In the SDG era of "leaving no one behind" acknowledging and addressing the unmet needs of women 50+ is from a public health perspective an issue of utmost urgency as is closing the gap between research, policy and practice. Conclusions: New strategies to improve health care services for women 50+ were developed by integrating the evidence from actual data in meaningfull dialogues between research, policy and practice. Key messages: New models of health care provision are required to adress and improve the health of women 50+. Closer collaboration between research policy and practice can be achieved by participatory methods.